Prevalence and associated risk factors for Lawsonia intracellularis infection in farmed rabbits: A serological and molecular cross-sectional study in South Korea - Yeh, Jung-Yong (Frontiers in Veterinary Science, 2023)
Lawsonia intracellularis is the etiological agent of proliferative enteropathy, which is globally considered an important enteric disease in pigs and horses. Experimental studies suggest that the organism spreads by subclinical infection of many animals, including rabbits. Despite the importance of rabbits in the epidemiology of L. intracellularis, the extent of exposure to L. intracellularis in the rabbit population is poorly defined and remains unclear. The objective of this cross-sectional study was to investigate the seroprevalence and shedding of L. intracellularis in farmed rabbits. Furthermore, we aimed to identify risk factors associated with seropositivity. Sera from the rabbits were used to measure L. intracellularis-specific antibodies by immunoperoxidase monolayer assay, and rectal swabs were used to detect L. intracellularis DNA using a real-time PCR assay. Antibodies against L. intracellularis were detected in 12.3% of farms (20/163) and 6.3% of rabbits (49/774). L. intracellularis DNA in rectal swabs was detected in 3.8% of farms (6/156) and 1.2% of rabbits (8/667). The risk factor analysis showed that the presence of pigs or horses on the farm or the neighboring farm was associated with an increase in the risk of seropositivity (p < 0.05). We observed significantly increased odds of positivity for L. intracellularis in rabbits with a history of digestive trouble (diarrhea) on the farm during the 3 months before the samples were obtained (p < 0.05). Collectively, these findings demonstrated that L. intracellularis infection was evident among farmed rabbits and that rabbits might serve as an important reservoir for L. intracellularis epidemiology.